The effect of return on equity, earning per share and price earning ratio on stock prices - Yuli Anwar (STIE Binaniaga, 2019)
The purpose of this study is to analyze, test, and prove the effect of returns on equity (ROE), earnings per share (EPS), and price-earnings ratio (PER) on stock prices (SP). The method carried out in this test uses multiple linear regression with the preceding test of classical assumption deviations. The result shows that the data is normally distributed and no overlapping is obtained. Based on the results of the ANOVA test calculations obtained the value of F-value = 13.349 with a significance of 0.005. By using the 0.05 level of significance, the value of F-table is 2.839. Then Fvalue 13.349> F-table (2.389), or significance of 0.005 smaller than 0.05 so that it can be concluded that the three independent variables namely ROE, EPS and PER simultaneously influence the Stock Price on the Indonesia Stock Exchange. Partially the ROE has a significant effect but EPS and PER do not affect. Keywords: returns on equity, earnings per share, and price-earnings ratio on stock prices.